A2MIPARI (Aksi Anak Membaca Iqra’ Pagi Hari); Pembelajaran Al-Qur’an pada Pendidikan Anak Usia Dini “Ash-Shiby” - Akbar, Eliyyil (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2017)
The children is a sensitive time which is something that he obtained is easily drenched with how to learn while playing. The habit of children playing can be made reference to become the habit of learning, so that the same used to play and learn. The habit of learning to read the Qur'an is done by repeatedly as consequence of Early Child Education